Realismo e Modernidade em Grande Sertão: veredas - Alysson Quirino Siffert (2017)
This essay seeks to investigate the authentic realism present in Grande Ser-tão: Veredas, based on aesthetic principles elaborated by György Lukács and other Marxist philosophers. Therefore, it represents an original work in the studies on the novel of João Guimarães Rosa, whose artistic work is usually studied separated to any notion of realism. Questioning this critical trend is part of the effort to demonstrate the multiple realistic aspects of this book. In this sense, our basic hypothesis is that the Grande Sertão: Veredas is capable of being a portrait of Brazil while singling out regional characters and incorporating decisive universal movements of modernity, de-termined by the advance of capitalism. In order to prove this hypothesis, this work investigates the dialectical logic present in the most diverse layers of the novel, paying special attention to the artistic condensation of different temporal and spatial dimensi-ons, viewed from the perspective of "unequal and combined development" and the real and aesthetics correlations of the categories of singularity, particularity and universa-lity. It dedicates a chapter to point out how Brazilian reality is incorporated into the characters and formal details of the novel, and another chapter to discuss the meanings of the Faust myth for universal literature and for the Guimarães Rosas novel. Finally, the concluding chapter proposes an interpretive neologism that unites the history and the story, and ends with words about the brutality and violence that mark this novel and Brazil.